139k views
2 votes
Please help and show work!!

Please help and show work!!-example-1

2 Answers

3 votes

Step 1. Use the Multiplication Distributive Property

So, -2n^6y^5 * -6n^3y^2n^3y^3

Step 2. Take out the constants

-(2 * -6)n^6n^3n^3y^5y^2y^3

Step 3. Simplify 2 * -6 to -12

-(-12)n^6n^3n^3y^5y^2y^3

Step 4. Regroup terms

-(-12n^6n^3n^3y^5y^2y^3)

Step 5. Use Product Rule

-(-12n^6 + 3 + 3 y^5 + 2 + 3)

Step 6. Simplify 5 + 2 + 3 to 10

-(-12n^12y^10)

Step 8. Simplify brackets

12n^12y^10

User Cristian Reyes
by
5.0k points
3 votes

​(-2n⁶y⁵)(-6n³y²)(ny)³ = We can take out the constants

= (12)(n⁶y⁵)(n³y²)(n³y³) = We can group the same variables

= (12)(n⁶)(n³)(n³) * (y⁵)(y²)(y³) = We can use the power product rule

=​(12)(n⁽⁶⁺³⁺³⁾) * (y⁽⁵⁺²⁺³⁾) = We add the exponents

Answer : 12n¹²y¹⁰​

​Hope this helps!​​​​


\textit{\textbf{Spymore}}​​​​​​

User Cgee
by
6.1k points